RABIES: UNITING FOR ONE HEALTH - PROTECTING HUMANS AND ANIMALS TOGETHER - HASSNAIN, M; HASHMI, HA; FATIMA, R; MUHAMMAD, A; REHMAN, MU; TEHREEM, A; HASSAN, HSZU; AHMED, N; KHAN, AMA; BASHARAT, A (Biological and Clinical Sciences Research Journal, 2024)
This review article elucidates the intricate dynamics of rabies and its effects in the context of a persistent global threat using the One Health approach. This article emphasizes the inescapable link between human, animal, and environmental health by clarifying the complex mechanisms of rabies transmission, elaborating on its symptoms and course, and demonstrating its global occurrence and impact. This article highlights the crucial importance of zoonotic diseases, notably the reservoir role of animals in rabies transmission, and embraces the idea of One Health, which recognizes the symbiotic interactions between these domains. This study highlights the significance of unified control and surveillance systems from a strategic perspective. This emphasizes the value of vaccination as a cornerstone for safeguarding both human and animal populations. Additionally, it highlights the potential of interdisciplinary One Health initiatives to eradicate rabies through successful case studies. This article sheds light on the crucial role of international organizations, the significance of policy advocacy, strict regulation, and international cooperation while addressing socioeconomic consequences, implementation challenges, and the goals of a rabies-free world. Interdisciplinary research has emerged as a catalyst to develop innovative prevention and control methods that are strengthened by technology, shared knowledge, and resilient strategies to combat the effects of climate change and emerging diseases. Public engagement, education, and community empowerment should be implemented to establish a proactive approach to rabies prevention. It concludes with a loud appeal for coordinated One Health initiatives to build a safer future in the face of this ongoing issue.